Effect of the use of a mixture of gluconeogenic compounds in dairy cows in transition - Arita-Portillo, Carlos Rafael (2023)
Introduction. During the transition period, dairy cows undergo great metabolic changes, due to the end of pregnancy and the beginning of lactation. During this period, most cows have a negative energy balance, due to the reduction in dry matter intake and the increase in energy requirements, thus in order to supply the needed energy, body reserves are mobilized. Objective. Evaluate the effect of the inclusion of a mixture of gluconeogenic compounds (propylene glycol, calcium propionate and sodium propionate) on productive parameters of transition cows. Materials and methods. The study was carried out in San Carlos, Alajuela, Costa Rica, between of June and October of 2020. 400 g of the mixture of gluconeogenic compounds were offered from day 21 before calving until 21 days postpartum. Eighteen multiparous cows were assigned to one of the two treatments: cows that consumed the mixture of gluconeogenic compounds (PG) and cows that did not consume the mixture of gluconeogenic compounds (TG). Live weight, body condition, blood glucose and beta-hydroxybutyrate concentrations, milk production and its components were measured. Results. Treatment did not affect live weight, body condition and milk production. Significant differences were observed in glucose concentrations 7 days before parturition, being higher for PG than for TG (p<0.05). Beta-hydroxybutyrate concentrations were higher for TG than for PG (p<0.05) on days 7 and 21 postpartum. Total solids and fat concentrations in milk were higher for TG than PG (p<0.05) on day 7 postpartum. Conclusion. Results suggest that supplementation with a mixture of gluconeogenic compounds improves the energy balance of dairy cows in transition.